2002
DOI: 10.1152/jn.00609.2001
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Spinobulbar Lamina I Neurons by Static Muscle Contraction

Abstract: . Activation of spinobulbar lamina I neurons by static muscle contraction. J Neurophysiol 87: 1641-1645, 2002; 10.1152/jn.00609.2001. Spinal lamina I neurons are selectively activated by small-diameter somatic afferents, and they project to brain stem sites that are critical for homeostatic control. Because small-diameter afferent activity evoked by contraction of skeletal muscle reflexly elicits exercise-related cardiorespiratory activation, we tested whether spinobulbar lamina I cells respond to muscle contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 20 publications
3
39
1
Order By: Relevance
“…In hypertension, combined or individual activation of either the mechanical (i.e., mechanoreflex) or metabolic component (i.e., metaboreflex) of the EPR results in a heightened sympathetically mediated cardiovascular response (2,13,22,23,34,38). To date, however, the mechanisms underlying EPR overactivity in hypertension remain largely unknown.The nucleus tractus solitarius (NTS) within the medulla oblongata of the brainstem is a central site of integration for sensory information from skeletal muscle afferents fibers (7,26,42). As evidence, anterograde tracing with biotinylated dextran amine of ascending neuronal projections from the spinal cord, to which skeletal muscle afferents contribute, has demonstrated that these fibers project to the NTS (30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In hypertension, combined or individual activation of either the mechanical (i.e., mechanoreflex) or metabolic component (i.e., metaboreflex) of the EPR results in a heightened sympathetically mediated cardiovascular response (2,13,22,23,34,38). To date, however, the mechanisms underlying EPR overactivity in hypertension remain largely unknown.The nucleus tractus solitarius (NTS) within the medulla oblongata of the brainstem is a central site of integration for sensory information from skeletal muscle afferents fibers (7,26,42). As evidence, anterograde tracing with biotinylated dextran amine of ascending neuronal projections from the spinal cord, to which skeletal muscle afferents contribute, has demonstrated that these fibers project to the NTS (30).…”
mentioning
confidence: 99%
“…The nucleus tractus solitarius (NTS) within the medulla oblongata of the brainstem is a central site of integration for sensory information from skeletal muscle afferents fibers (7,26,42). As evidence, anterograde tracing with biotinylated dextran amine of ascending neuronal projections from the spinal cord, to which skeletal muscle afferents contribute, has demonstrated that these fibers project to the NTS (30).…”
mentioning
confidence: 99%
“…Future studies should verify whether this 5-HT 1A Rgated lumbar spinoparabrachial respiratory-inhibiting pathway is glutamatergic (impinging on a respiratory-inhibiting network in LPBN-KFN) or GABAergic/glycinergic (impinging on a respiratory-exciting network). In addition, somatic afferents (e.g., those from skeletal muscles) may also be relayed by spinal lamina I neurons directly to the medullary respiratory circuits (Wilson et al 2002). Whether this pathway is also subject to 5-HT 1A Rgating remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (4, 5) using electrophysiological methods have also shown that neurons in the superficial and deep dorsal horn at the L7 level are excited during muscle contraction. Furthermore, it has recently been shown that the lamina I neurons of the dorsal horn that project to the caudal ventrolateral medulla are activated by static muscle contraction (40). In addition, the codistribution of c-Fos neurons and NOS-positive staining in this region of the superficial horn was determined by a double-label method and provided a unique opportunity to determine the neurochemical characteristics of activated neurons.…”
Section: Discussionmentioning
confidence: 99%